The effect of dwelling size on the mental health and quality of life of female caregivers living in informal tiny homes in Hong Kong - Crystal Ying Chan; Ruby Yuen Shan Lai; Becky Hoi; Maggie Ying Yee Li; Joyce Ho Yi Chan; Henry Ho Fai Sin; Edwin Shun Kit Chung; Rowan Tak Yuen Cheung; Eliza Lai Yi Wong (BMC, 2024)
Abstract Background Although the adverse impact of substandard informal housing has been widely documented, most studies concentrated on developing societies, thereby leaving informal housing in developed regions underexplored. This study examines Hong Kong, where limited dwelling size is a distinctive feature that characterises informal housing, to explore the impact of housing informality on mental health, with a particular focus on dwelling size. It centers on subdivided units (SDUs), which are tiny compartments partitioned from a large domestic quarter, to understand how housing informality and housing size affect the mental well-being of female caregivers, who typically bear the brunt of the housework. Methods In partnership with nongovernment organisations in three SDU-abundant districts, this mixed-methods study conducted a survey on 413 female caregivers aged 18-65 and qualitative research combining ethnographic observations and in-depth interviews on 36 families living in SDUs in Hong Kong between 2021 and 2023. The mental health outcomes and health-related quality of life (HRQoL) of the participants were assessed by using the Depression, Anxiety, and Stress Scale-21 and a EuroQol-5 Dimension-5 Level questionnaire. Results Depression, anxiety and stress were prevalent across the female caregivers living in SDUs (12.4%), as well as a significantly lower HRQoL compared with that of the general population (0.882 vs. 0.919). Findings showed that a total floor area smaller than 13.0 m2 was associated with increased likelihood of experiencing anxiety and depression and reduced HRQoL. Cramped living space adversely affected the caregivers' well-being through the 1) physical, 2) relational and 3) personal aspects of home experiences. Negative experiences at home can cause housework burnout, exacerbate family conflicts and lead to feelings of repression and low self-efficacy. Conclusions This study contributes to the understanding of the consequences of housing informality in diverse geographical contexts and illuminates the effect of dwelling size by identifying the mechanisms through which housing size can affect the mental well-being of residents, which may vary depending on their family status. The findings yield important policy implications, including the need to establish a minimum space standard for subdivided residential dwellings and ensure equitable access to community spaces for deprived families.